Trends in Spouses’ Shared Time in the United States, 1965–2012 - Genadek, Katie R. (Demography, 2016)
Despite major demographic changes over the past 50 years and strong evidence that time spent with a spouse is important for marriages, we know very little about how time with a spouse has changed—or not—in the United States. Using time diary data from 1965–2012, we examine trends in couples’ shared time in the United States during a period of major changes in American marriages and families. We find that couples without children spent more total time together and time alone together n 2012 than they did in 1965, with total time and time alone together both peaking in 1975. For parents, time spent together increased between 1965 and 2012, most dramatically for time spent with a spouse and children. Decomposition analyses show that changes in behavior rather than changing demographics explain these trends, and we find that the increases in couples’ shared time are primarily concentrated in leisure activities.